2018
DOI: 10.20944/preprints201809.0040.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

TREM-1; is It a Pivotal Target for Cardiovascular Diseases?

Abstract: Cardiovascular Diseases (CVDs) are still menacing and killing adults worldwide, notwithstanding the tremendous effort, to decrease their related mortality and morbidity. Lately, a growing body of evidences indicated that inflammation plays a pivotal role in the pathogenesis and complications of CVDs. A receptor of the immunoglobulin superfamily, triggering receptor expressed on myeloid cells -1 (TREM-1) was shown to induce and to amplify the inflammation in both acute and chronic diseases pathogenesis and prog… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 77 publications
0
6
0
Order By: Relevance
“…Many chemokines, in addition to psoriasis, are found in the pathogenesis of other inflammatory diseases and also represent potential therapeutic targets for them. This has been confirmed for generalized pustular psoriasis [ 6 ], psoriatic [ 7 , 8 ] and rheumatoid arthritis [ 9 ], cardiovascular disease [ 10 , 11 ], atherosclerosis [ 12 ], obesity [ 13 ], metabolic syndrome [ 14 ] and atopic dermatitis [ 15 , 16 , 17 ], irritant dermatitis [ 16 ], thyroiditis [ 18 ] or Schnitzler syndrome [ 19 ].…”
Section: Introductionmentioning
confidence: 93%
“…Many chemokines, in addition to psoriasis, are found in the pathogenesis of other inflammatory diseases and also represent potential therapeutic targets for them. This has been confirmed for generalized pustular psoriasis [ 6 ], psoriatic [ 7 , 8 ] and rheumatoid arthritis [ 9 ], cardiovascular disease [ 10 , 11 ], atherosclerosis [ 12 ], obesity [ 13 ], metabolic syndrome [ 14 ] and atopic dermatitis [ 15 , 16 , 17 ], irritant dermatitis [ 16 ], thyroiditis [ 18 ] or Schnitzler syndrome [ 19 ].…”
Section: Introductionmentioning
confidence: 93%
“…Indeed, curcumin was shown to attenuate cardiac hypertrophy, fibrosis and dysfunction by inhibiting p300-mediated GATA4 acetylation [25]. The ability of curcumin to inhibit p300 activity was further shown to inhibit pro-inflammatory gene expression, specifically triggering receptors expressed on myeloid cells-1 (TREM-1) [27], that induce atherosclerosis and myocardial infarction [28]. Thus, inhibiting p300 seems to be an important mechansistic action of curcumin for its cardioprotective role.…”
Section: Curcumin and Histone Acetylation In Cvdmentioning
confidence: 99%
“…In this context, there has also been a revival of interest in the clinical utility of measurement of circulating soluble triggering receptor expressed on myeloid cells (sTREM‐1), described in an earlier study as being a useful pro‐inflammatory biomarker in the diagnosis and prognosis, including mortality, in patients with severe all‐cause CAP . A more recent study has identified sTREM‐1 as being a contributor to the pathogenesis of acute and chronic CV conditions, including AMI, with the authors contending that measurement of this biomarker has significant implications for diagnosis, management and prognosis of CV disorders .…”
Section: Biomarkers Of Myocardial Damagementioning
confidence: 99%